Innovating Language Instruction in Madrasah Diniyah: The Use of English Storytelling to Enhance Speaking Skills and Learner’s Well-Being - Farid Noor Romadlon; Rusiana; Nuraeningsih; Agung Dwi Nurcahyo; Abdul Rasheed; Yaqqob, Nur Syafiqah (Journal of English Teaching and Linguistic Issues (JETLI), 2025)
Madrasah Diniyah institutions often face persistent challenges in language instruction, including low student engagement and limited diversity in teaching methodologies. These issues can hinder both linguistic development and overall learner well-being. To address this concern, this study explores the integration of English storytelling as a pedagogical strategy to (1) promote students’ speaking skills and (2) promote their emotional and psychological well-being during the learning process. Employing a Classroom Action Research (CAR) design, the study was conducted over two instructional cycles involving 52 students from Madrasah Diniyah Kanzul Ulum. Data were collected through both quantitative and qualitative methods. Pre-tests and post-tests assessed improvements in speaking performance, focusing on fluency, vocabulary usage, and overall comprehension. Qualitative data were obtained through classroom observations, student questionnaires, and semi-structured interviews with parents to capture behavioral and emotional responses to the intervention. The findings indicate a significant improvement in students’ speaking abilities, with notable gains in verbal expression, confidence, and classroom engagement. Storytelling sessions fostered a dynamic and enjoyable learning environment, encouraging active participation and reducing student anxiety. Furthermore, students developed a stronger emotional connection to the material, which enhanced motivation and fostered a more positive attitude toward learning English. Parental feedback also revealed increased use of simple English expressions at home and greater enthusiasm for attending classes. These outcomes suggest that English storytelling not only supports language acquisition but also contributes to students’ holistic development. Accordingly, it presents a promising instructional approach for enhancing both linguistic proficiency and well-being in non-formal Islamic educational settings.